PENGARUH STRUKTUR MODAL, PEMEGANG SAHAM DEWAN DIREKSI, DAN PEMEGANG SAHAM KELUARGA TERHADAP KINERJA KEUANGAN - Syurti Primadayani; Femitri Eka Putri (Jurnal Daya Saing, 2026)
The objective of this research is to analyze the effect of capital structure, board, and family shareholder on financial performance on the all of companies listed in Indonesia Stoct Exchange (BEI). The type of data is secondary data from the financial statements for 2013 to 2015. The sample of this research is 366 companies listed in indonesia stock exchange. The result showed that capital structure, board shreholders, family shareholder, profitabily, and leverage has a positive and significant effect on financial performance. Capital structure has a negatif and unsignificant effect on financial performance. Board shareholders has a negative and unsignificant effect on financial performance. Family shareholder has a positive and unsignificant effect on financial performance. Control variable: profitability has a positive and significant effect on financial performance, and leverage has a positive and unsignificant effect on financial performance